2020
DOI: 10.1371/journal.pone.0232463
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after transabdominal cerclage in twin pregnancy with previous unsuccessful transvaginal cerclage

Abstract: Transabdominal cerclage (TAC) is reported to be effective for preventing preterm birth in women with unsuccessful transvaginal cerclage (TVC) history. However, TAC has rarely been performed in twin pregnancy given the lack of sufficient evidence and the technical difficulty of the operation. Thus, it is unclear whether TAC is an effective procedure for twin pregnancy in women with a history of unsuccessful TVC. The aim of this study is to compare the characteristics and pregnancy outcomes after TAC in twin pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Patients with a TAC should be delivered by cesarean section. Although there is no consensus on the exact timing of delivery, a 37 to 39-week range is commonly used with the intention of avoiding cervical damage or uterine rupture that may be caused by labor [26,32].…”
Section: Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a TAC should be delivered by cesarean section. Although there is no consensus on the exact timing of delivery, a 37 to 39-week range is commonly used with the intention of avoiding cervical damage or uterine rupture that may be caused by labor [26,32].…”
Section: Deliverymentioning
confidence: 99%
“…Contraindications for TAC are similar to that of TVC and include active intrauterine infection, preterm labor, PPROM, bleeding, and fetal demise. Twin gestation is not a contradiction, and two studies have shown improved neonatal survival rates in twin pregnancies following TAC placement in appropriate candidates [32,33].…”
Section: Contraindicationsmentioning
confidence: 99%